1979
DOI: 10.1161/01.res.44.6.864
|View full text |Cite
|
Sign up to set email alerts
|

Effects of some components of ischemia on electrical activity and reentry in the canine ventricular conducting system.

Abstract: We used intracellular microelectrodes to study the electrophysiological effects of combinations of components of ischemia and their relation to the occurrence of ventricular arrhythmias in the specialized conducting system of isolated canine right ventricles. The middle area of the free wall was exposed to various test solutions in the center compartment of a three-chambered bath; the base and apex of the preparation were superfused with normal Tyrode's solution in the outer control compartments. Hypoxia (Po2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
9
0

Year Published

1979
1979
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 36 publications
5
9
0
Order By: Relevance
“…lar Purkinje fibers providing no evidence of increased focal automaticity. Furthermore, in the presence of regional hypoxia and acidosis no reentrant tachycardia could be induced despite marked alterations of the local refractory periods (19). The important common fa~ in both hypoxia and acidosis was that they failed to cause a conduction delay confirminl earlier results (1, 3, 10, 21).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…lar Purkinje fibers providing no evidence of increased focal automaticity. Furthermore, in the presence of regional hypoxia and acidosis no reentrant tachycardia could be induced despite marked alterations of the local refractory periods (19). The important common fa~ in both hypoxia and acidosis was that they failed to cause a conduction delay confirminl earlier results (1, 3, 10, 21).…”
Section: Discussionsupporting
confidence: 74%
“…Hypotheses concerning possible characteristics of electrical activity in ischemic or infarcting myocardium has been derived from results of electrophysiological studies on isolated ventricular tissues exposed to such substances that may be present in the ischemic environment (1,3,5,10,20). Previous results obtained from an in-vitro model of regional ischemia using a three-chambered bath have indicated that hypoxia, acidosis or catecholamines, either alone or combined, did not provoke ventricular arrhythmias and that regional increase in extracellular K § was the predominant arrhythmogenic factor (19).…”
Section: Introductionmentioning
confidence: 99%
“…Various drugs, including the calcium channel-blocking agents, are capable of suppressing these arrhythmias.14 15 Although the mechanism(s) by which the calcium-blocking agents suppress arrhythmias remains uncertain, several potentially antiarrhythmic effects of various members of this class of agents have been demonstrated in the setting of acute ischemia. These include (1) a decrease in the size of an experimental infarct zone,16 (2) a lessening in the delay in local activation, '7-20 (3) metabolic protection of the ischemic tissues,2' 24 and (4) a decrease in the rate of [K']e accumulation.25 27 However, the effects of calcium blockers on the metabolic, electrical, and ionic changes during ischemia have not been correlated in the same experimental preparation. Nor have these effects been demonstrated in an experimental preparation with low collateral flow, such as the pig.28 '29 We have recently reported that serial 10 min coronary occlusions in the swine heart in situ provide a useful method of studying the ischemia-induced changes in myocardial [K] Miniature K'-sensitive and H+-sensitive plunge electrodes, modified from earlier designs,10 were fashioned by methods described in detail elsewhere.…”
mentioning
confidence: 99%
“…Acidification is an early and important biochemical change associated with acute myocardial ischaemia (Elliott et al 1992, Vandenberg et al 1993) and may contribute importantly to the enhanced risks of potentially life-threatening arrhythmias in such situations (Senges et al 1979, Luqman et al 2007). The mechanisms underlying arrhythmogenicity in metabolic acidification have therefore attracted extensive study (Orchard & Cingolani 1994).…”
mentioning
confidence: 99%